Early Stages of the Natriuretic Hormone Story - Lichardus, Branislav (Frontiers in Endocrinology, 2014)
The paper reviews the early stages of the research on natriuretic hormone. The described experimental work was designed and accomplished in several internationally recognized laboratories where the author was invited to extend his projects. The cross-circulation experiments in animals with acutely increased extracellular fluid volume documented, that in the mechanism of natriuresis - besides a series of the physical natriuretic factors - there is still room for an active humoral natriuretic substance. This substance impaired the activity of the sodium transporting enzyme, Na,K – ATPase, in the frog skin. Analogous impairment of sodium transporting enzyme may be partly responsible for the increased sodium excretion. It was further shown that the extent of natriuresis is positively modulated by the concentration of sodium in the cerebro - spinal fluid detected in the anterior third ventricle region (A3V) in the brain.